Model Bisnis dan Daya Saing Hotel E-sports: Bukti Empiris dari Tiongkok dan Prospek Implementasi di Indonesia - Felix Goenadhi; Zhang Boxiang (Lentera Ilmu Madani, 2026)
This study focuses on the business model and competitiveness of e-sports hotels by drawing empirical insights from China, particularly the case of Henan Province, and translating these lessons into practical implementation strategies for Indonesia. Using a qualitative-descriptive approach based on secondary data, case analysis, and industry reports, the research examines dominant business models, sources of competitive advantage, and structural challenges faced by e-sports hotels in China. The findings indicate that successful e-sports hotels rely on hybrid business models combining direct operation, franchising, and event-based revenue streams, supported by standardized service quality and strong ecosystem partnerships. However, market homogenization, talent shortages, and inconsistent service quality remain key constraints. Building on these insights, the study proposes an implementation framework for Indonesia that integrates e-sports hotels with tourism destinations and local creative economies. Furthermore, the paper outlines a future research agenda focusing on Indonesia’s ten priority tourism destinations as designated by the Ministry of Tourism and Creative Economy. The study contributes to hospitality and tourism management literature by offering a cross-country perspective on how e-sports hotels can enhance competitiveness through adaptive business models in emerging tourism markets